Construção de um instrumento para predição de risco de úlcera por pressão de uso domiciliar para idosos acamados atendidos na Estratégia Saúde da Família - Silva, Maria do Socorro Moura Lins (2014)
Introduction: There are 39 scales for predicting the development risk of pressure ulcer (PU), for the adults/elderly individuals for use by health professionals, especially nurses but only one was made up for use in the communitarian level. Objective: To construct a scale for predicting pressure ulcer risk of home use for the bedridden individuals cared in the Family Health Strategy (FHS). Methods: A study was carried out in five stages: (I) observational study of elderly individuals with and without PU (observational, participant and cross-sectional piece of research); (II) construction of a pressure ulcer (PU) prediction tool in the elderly; (III) analysis of the tool constructed in the stage II by the specialists committee; (IV) semantic analysis of the tool; (V) use of the tool in a sample of the elderly without PU (longitudinal and observational piece of research carried out in a sample of the bedridden elderly individuals registered in the FHP of the Distrito Sanitário de Saúde III in João Pessoa-PB, Brazil). Results: The main results of each stage were: (I) 13 risk factors for PU were identified in bedridden elderly individuals with and without PU; (II) a tool containing 17 items was made up; (III) an analysis was carried out by specialists remaining 16 items; (IV) after the semantic analysis, some adjustments were fulfilled in the tool; (V) the tool was used in 92 bedridden elderly individuals. The elderly´s average age was 83,3 years old ( 60-10 years). It was female predominant (64,4%) having their family members (95,6%) as caretaker and they presented two or more morbidities (72%). Systemic hypertension, cerebrovascular accident (CVA) and diabetes mellitus were the most frequent diseases (66%, 56% and 30%, respectively). Thirteen elderly individuals presented PU (14,4%). Taking into account the predisposing factors, nine were meaningfully more common among the elderly with PU rather than those who did not present such condition: general health condition, weight loss, bed mobility, skin exposure to moisture, body hygiene incontinence;predisposing morbidities, awareness level and superficial sensitivity (P<0,05). A decreasing classification of magnitude with the associations of all factors and the presence of PU was carried out by using the logistic score test: general health condition (28,097), bed mobility (24,944), skin exposure to moisture (18,540) and weight loss (17,852) were the most leading factors. By means of the odds ratio (OR) method, it was noticed that the same factors were also predominant amongst the others. In an additional refining, the three factors of highest magnitude of association with PU were combined in a risk score. Such risk score presented points varying from 0 to 5 and it signaled the condition of each elderly individual in relation to these three factors. The elderly who had low score (score ≤ 2) did not present PU. In those with 3 points, there was the presence of PU (42%). All the elderly individuals with 4 or more points in the score presented PU (N= 8).